The Influence of Lifestyle and Financial Planning on Islamic Stock Investment Decisions in a Digitally Mediated Environment - Djunaidi, Zikri Habibi; Imsar, Imsar; Anggraini, Tuti (Celebes Scholar pg, 2025)
The speeding up of the digitalization of financial life that accompanies a rising cultural discourse about ethical investment is transforming the habits that shape the economic decisions of young Muslims. The current research examines how Islam stock investment could be impacted by lifestyle preferences and individual financial planning of student at the State Islamic University of North Sumatra (UINSU) relative to Jakarta Islamic Index (JII). Using a quantitative research approach on Structural Equation Modeling- Partial Least Squares (SEM-PLS) students investors active securities accounts were sampled and 94 student investors were selected. The results indicate that both lifestyle and financial planning influence investment decisions positively and independently of each other and lifestyle has a stronger effect in predicting investment decision. These findings indicate that approval of financial behavior of students is not a matter of systematic planning or technical literacy; there are extensive rationales on the basis of social identity, aspiration norms, and daily practices. In this environment, investment is identified as a mode of defining ethical orientation, social spot, and future intention, and not expressed as a pure economic concept. The study sets Islamic investing in the real world of digitally connected and religiously minded youngsters, enhancing the interpretation of behavioral finance in faith-related situations. It points a finger towards educational and institutional paradigms that take the financial decision-making beyond transactional competence, to cover ethical, cultural and social aspects of financial decision-making.